Evaluating the impact and use of Transparent Reporting of Evaluations with Non-randomised Designs (TREND) reporting guidelines. Issue 6 (19th December 2012) - Fuller, Thomas; Pearson, Mark; Peters, Jaime L; Anderson, Rob
Abstract : Introduction: Accurate and full reporting of evaluation of interventions in health research is needed for evidence synthesis and informed decision-making. Evidence suggests that biases and incomplete reporting affect the assessment of study validity and the ability to include this data in secondary research. The Transparent Reporting of Evaluations with Non-randomised Designs (TREND) reporting guideline was developed to improve the transparency and accuracy of the reporting of behavioural and public health evaluations with non-randomised designs. Evaluations of reporting guidelines have shown that they can be effective in improving reporting completeness. Although TREND occupies a niche within reporting guidelines, and despite it being 8 years since publication, no study yet has assessed its impact on reporting completeness or investigated what factors affect its use by authors and journal editors. This protocol describes two studies that aim to redress this. Methods and analysis: Study 1 will use an observational design to examine the uptake and use of TREND by authors, and by journals in their instructions to authors. A comparison of reporting completeness and study quality of papers that do and do not use TREND to inform reporting will be made. Study 2 will use a cross-sectional survey to investigate what factors inhibit or facilitate authors' and journal editors' use of TREND. Semistructured interviews will also be conducted with a subset of authors and editors to explore findings from study 1 and the surveys in greater depth. Ethics and dissemination: These studies will generate evidence of how implementation and dissemination of the TREND guideline has affected reporting completeness in studies with experimental, non-randomised designs within behavioural and public health research. The project has received ethics approval from the Research Ethics Committee of the Peninsula College of Medicine and Dentistry, Universities of Exeter and Plymouth.